Hyperbaric oxygen therapy in sports musculoskeletal injuries - Moghadam, N.; Hieda, M.; Ramey, L.; Levine, B. D.; Guillod, R. (Medicine & Science in Sports & Exercise, 2020)
Hyperbaric oxygen therapy (HBOT) is a well-established treatment for a variety of conditions. Hyperbaric oxygen therapy is the administration of 100% oxygen breathing in a pressure vessel at higher than atmospheric pressure (1 atmosphere absolute = 101 kPa). Typically, treatment is given daily for between 1 and 2 h at pressures of 2.0 to 2.8 ATA, depending on the indication. Sporting injuries are often treated over 3 to 10 sessions. Hyperbaric oxygen therapy has been documented to be effective and is approved in 14 medical indications by the Undersea and Hyperbaric Medical Society, including, but not limited to, carbon monoxide poisoning, compromised skin grafts and flaps, crush injuries, necrotizing soft tissue infections, and nonhealing ulcers with arterial insufficiencies. Recently, HBOT for sports musculoskeletal injuries is receiving increased attention. Hyperbaric oxygen therapy may allow injured athletes to recover faster than normal rehabilitation methods. Any reduction in collegiate and professional athletes` rehabilitation period can be financially significant for top-level sports teams; however, further research is required to confirm HBOT`s benefits on sports musculoskeletal injuries. The purpose of this review to discuss the current understanding of HBOT as a treatment modality for common musculoskeletal injuries in sport medicine. Moreover, we will highlight the advantages and disadvantages of this modality, as well as relevant clinical and research applications.